Combinatorial algebraic approach for modified second-generation time-delay interferometry - Wu, Zhang-Qi; Wang, Pan-Pan; Qian, Wei-Liang [UNESP]; Shao, Cheng-Gang (American Physical Society (APS), 2023)
We generalize the combinatorial algebraic approach first proposed by Dhurandhar et al. to construct various classes of modified second-generation time-delay interferometry (TDI) solutions. The main idea behind the original algorithm is to enumerate, in a given order, a specific type of commutator between two monomials defined by the products of particular time-displacement operators. On the one hand, the enumeration process can be implemented using the properties of the commutative ring and the relevant equation for the TDI solution. On the other hand, these commutators are shown to vanish if we only keep up the first-order contributions regarding the rate of change of armlengths. In other words, each commutator furnishes a valid TDI solution pertaining to the given type of modified second-generation combinations. In this work, Dhurandhar's algorithm, which only involved time-delay operators and was primarily applied to Michelson-type solutions, is extended by introducing the time-advance ones and then utilized to seek combinations of the Beacon, Relay, Monitor, Sagnac, and fully symmetric Sagnac types. We discuss the relation between the present scheme's solutions and those obtained by the geometric TDI approach, a well-known method of exhaustion of virtual optical paths. In particular, we report the results on novel Sagnac-inspired solutions that cannot be straightforwardly obtained using the geometric TDI algorithm. The average response functions, floor noise power spectral densities, and sensitivity functions are evaluated for the obtained solutions.